Virulence in Rats of Gentamicin-Carbenicillin-Resistant Pseudomonas - Slepack, Jerry M. (1975)
Strains of Pseudomonas aeruginosa, with resistance to gentamicin and carbenicillin which is R factor mediated, showed no alteration in virulence as tested by intraperitoneal injection of rats.